Life: Full house! Lonely planet? (Three Big Questions) - Rolston, Holmes, 1932-2025, speaker; Antolin, Michael, speaker; McKay, John, speaker (Colorado State University. Libraries, 2012)
Where once there were no species on Earth, there are today five to ten million. Information coded in DNA, a "cybernetic" molecule makes possible a creative upflow of life struggling through turnover of species and resulting in more diverse and complex forms of life, producing a wonderland of biodiversity. Life is ever "conserved," biologists might say; life is perpetually "redeemed," theologians might say. Is such creative evolutionary natural history probable, improbably, lucky, random, ordered, disordered, inevitable? Is wonderland Earth a lonely planet? What of the human responsibility to respect life? Is life sacred? A gift?
With commentary by Michael Antolin and John McKay. Recorded March 22, 2012.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.